ASSESSMENT OF RURAL GIRLS' PHYSICAL FITNESS THROUGH A CLASSIFIED METHODOLOGY (Scientific journal of the Fergana State University, 2024)
It serves as a basis for comprehensive pedagogical research aimed at improving the system of physical education in rural educational institutions with the introduction of modern innovative pedagogical technologies into the educational process.